Prediction of potential geographic distribution of exotic nematode, Aphelenchoides fragariae in India based on MaxEnt ecological niche modelling - Holajjer, Prasanna; Gawade, Bharat H; Khan, Z; Sivaraj, N (Indian Journal of Plant Protection, 2022)
Strawberry crimp nematode, Aphelenchoides fragariae is an important ecto- and endoparasite affecting several plant species including ornamental plants. This nematode is polyphagous and invasive in nature, not reported to occur in India and has been listed as a quarantine pest in India. Understanding suitable habitat and potential geographic distribution of A. fragariae in India would greatly help to know its establishment and the extent of spread. The maximum entropy (MaxEnt) model was used in this study to identify potential geographic distribution in India under current climatic conditions. The MaxEnt model provided the reliable prediction of climate suitability for A. fragariae in India as measured by AUC values of 0.972 for training data and 0.942 for test data. The model identified highly suitable regions for A. fragariae that are mainly located in Northern and Eastern parts of India, such as Himachal Pradesh, Uttarakhand, Arunachal Pradesh and few places in Jammu and Kashmir. Among the bioclimatic variables, isothermality (Bio3) and precipitation of driest month (Bio14) have more influence on geographic suitability for A. fragariae as indicated with highest gain value in Jackknife test